Gas-Exchange Traits And Their Relationship To Water-Use Efficiency Of Grain-Sorghum - Peng, Shaobing; Krieg, Daniel R. (Wiley, 1992)
Bleeding for increased water use efficiency (WUE) has been limited by the lack of screening criteria and methods for selecting desirable genotypes from large populations under field conditions. The purpose of this experiment was to determine whether genetic variation in gas exchange traits reflects differences among sorghum genotypes [Sorghum bicolor (L.) Moench] in WUE and thus could be used as screening criteria. Five sorghum genotypes were grown in the greenhouse and field during 1989 under well‐watered conditions. In the greenhouse study, individual entries were planted in plastic pots. The field experiment was conducted on an Amarillo loamy fine sand (fine‐loamy, mixed, thermic Aridic Paleustalf). Shoot biomass production, water use, and leaf area development were determined. Gas exchange measurements were made throughout the vegetative stage on uppermost fully expanded leaves, using a portable photosynthesis systems. The sorghum genotypes exhibited significant and consistent variation in C assimilation rate (A), shoot biomass and leaf area production, and WUE. No consistent genotypic variation was observed for transpira. tion (T) or whole‐plant water use rates. Single leaf measurements of .4 reflected single‐plant and whole‐canopy WUE differences among the genotypes, largely due to the positive correlation between A and shoot biomass production. In addition, there was a positive correlation among the genotypes between leaf area and A. The results indicate that measurements of A and leaf area reflected biomass production, which was the primary determinant of water use efficiency, since minor nonsignificant differences existed among the genotypes in water use.